2017
DOI: 10.1093/heapol/czx020
|View full text |Cite
|
Sign up to set email alerts
|

Understanding public perception of the need for major change in Latin American healthcare systems

Abstract: The opinions and experiences of the public regarding health services are valuable insights into identifying opportunities to improve healthcare systems. We analyzed the 2012-2013 Public Opinion Health Policy Survey carried out in Brazil (n = 1486), Colombia (n = 1485), El Salvador (n = 1460), Jamaica (n = 1480), México (n = 1492) and Panama (n = 1475). In these countries between 82 and 96% of participants perceived that their health systems needed fundamental changes. The most frequent barrier to access to hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…We performed a secondary analysis of a recent (2013) public opinion survey focusing on perceptions and experiences with healthcare systems in 6 LAC countries: Brazil, Colombia, El Salvador, Jamaica, Mexico, and Panama. The detailed methodology of this survey was previously reported elsewhere [ 10 , 22 , 23 ]. In each country, the survey included a nationally representative urban sample of the population that comprised between 1,500 and 1,506 adults per country.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We performed a secondary analysis of a recent (2013) public opinion survey focusing on perceptions and experiences with healthcare systems in 6 LAC countries: Brazil, Colombia, El Salvador, Jamaica, Mexico, and Panama. The detailed methodology of this survey was previously reported elsewhere [ 10 , 22 , 23 ]. In each country, the survey included a nationally representative urban sample of the population that comprised between 1,500 and 1,506 adults per country.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to seeing the data, we identified the public opinion survey as a unique resource to test associations of healthcare quality and SRH in a representative, multi-country sample. We then reviewed the literature on patient-centered PC and identified 5 key domains (contact with clinic, time spent with provider, patient–provider communication, technical quality and solving problems, and healthcare coordination) relevant for patient-centered healthcare [ 10 , 23 , 25 , 26 ]; we mapped items from the survey to these domains and created single-item summaries as well as an overall score. We defined covariates based on relevance to health status and healthcare utilization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased access was the main focus during the development of norms of Ordinance n. 77/2017. Studies have shown that the poorest population suffers the greatest difficulties regarding access to health services 14 , and that there is significant demand for longer PHC working hours, including weekend availability 6,34 . Therefore, It was decided to expand the hours of the larger units to operate from 7 am to 7 pm, without interruption, and also on Saturdays from 7 am to 12 noon, with the possibility of operating until 10 pm.…”
Section: The Df Primary Health Care Reform Processmentioning
confidence: 99%